Pengembangan UMKM Kreatif Berbasis Experiential Marketing dengan Integrasi Healthy Tourism dan Spiritual Tourism pada Wilayah Aisyiyah Jawa Barat - Untung Novianto; Nina Gartika; Arsya Arba (Politeknik Piksi Ganesha Indonesia, 2025)
This community engagement program aims to enhance the capacity of the BUEKA community under the West Java Aisyiyah Regional Leadership by implementing experiential marketing integrated with healthy and spiritual tourism concepts. The activity applied the Participatory Action Research (PAR) method, focusing on empowering 20 members of the ABS Cooperative's UMKM group. The outcomes indicate a significant improvement in product development, spiritually rooted brand identity, and visitor involvement in healthy-religious tourism packages. Strengthening digital marketing, creating healthy-spiritual travel itineraries, and community engagement networks are strategic outputs that directly impact the partners’ capabilities and competitiveness.